Prediction of chronic endometritis using 2D and 3D transvaginal ultrasound examination in infertile women - Said, Tamer H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Chronic endometritis is a pathology of continuous and hidden inflammatory process characterized by the infiltration of plasma cells into the endometrial stroma. Transvaginal bi-dimensional ultrasonography is in need to be evaluated in prediction of chronic endometritis in women with delayed pregnancy or infertility as a non-invasive, cheap, acceptable, and safe tool of diagnosis. Previously, 3D ultrasonography had been described as a novel for diagnosis of chronic endometritis and correlation of the images with hysteroscopic view results. Objectives were to predict the presence of chronic endometritis in infertile women during their reproductive age through examination of the uterine cavity by 2D and 3D transvaginal sonography to elicit proposed ultrasonographic signs of endometritis. Methods: This observational prospective study took place at Shatby university hospital, Alexanderia universtiy and was done on two hundred infertile women. Women were assigned for ultrasonographic evaluation as a part of pre-treatment assessment. Detailed history was taken from all the patients included in the study. General examination and routine laboratory investigations were done according to hospital protocol. All patients were asked to do ultrasound examination immediately postmenstrual and at the time of ovulation. We used 2D transvaginal ultrasound to predict chronic endometritis, we searched for 1) presence of persistent endometrial focal or diffuse thickening postmenstrual, 2) presence of focal echogenic foci in the triple line endometrium during ovulation. The 3D ultrasonography was done as confirmatory examination. Office hysteroscopy as the main method for diagnosis of endometritis was performed to all patients either after menses if the first sign was detected or at the time of ovulation if the second sign was detected. Results: The combination of persistent endometrial shreds and/or endometrial focal thickening or echogenicity can significantly predict presence of endometritis as the sensitivity and specificity of the combination were 94.90 and 81.37, respectively. Conclusions: Bi-dimensional ultrasonography done to infertile women at 2 phases of the menstrual period can predict the presence of chronic endometritis as a subtle cause of infertility and might be an indication for hysteroscopic evaluation for these patients.